Learning mongoid : build scalable, efficient rails web applications with mongoid - Rege, Gautam (Community experience distilled., 2013)
A step-by-step tutorial with focused examples that will help you build scalable, high performance Rails web applications with Mongoid. If you are an application developer who wants to learn how to use Mongoid in a Rails application, this book will be great for you. You are expected to be familiar with MongoDB and Ruby.